2007
DOI: 10.1016/j.cardiores.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac peroxisome proliferator-activated receptor γ is essential in protecting cardiomyocytes from oxidative damage

Abstract: The present study demonstrates that PPARgamma is critical to myocardial redox homeostasis. These findings should provide new insights into understanding the roles of PPARgamma in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 36 publications
7
118
0
Order By: Relevance
“…34) Moreover, it is markedly expressed in rCMCs and protects them from oxidative stress. 35,36) In this study, we found that RSG significantly decreased H 2 O 2 -induced oxidative stress, and this effect was dependent on its ability to activate PPAR. Our data also suggest that most of the antioxidative activity of RSG is determined by its ability to activate TRx.…”
Section: Discussionmentioning
confidence: 49%
“…34) Moreover, it is markedly expressed in rCMCs and protects them from oxidative stress. 35,36) In this study, we found that RSG significantly decreased H 2 O 2 -induced oxidative stress, and this effect was dependent on its ability to activate PPAR. Our data also suggest that most of the antioxidative activity of RSG is determined by its ability to activate TRx.…”
Section: Discussionmentioning
confidence: 49%
“…This observation is consistent with the hypothesis that the CB 1 receptor agonist controls leptin action at least in part through PPAR-␥ activation. This nuclear receptor can directly regulate the expression of a large number of antioxidant enzymes, including catalase (9,28,29), which is ubiquitously expressed in the CNS and is mainly located in peroxisomes (8). In agreement with the report that PPAR-␥ activation by a specific agonist enhances catalase activity, thereby resulting in the protection of neurons from oxidative stress (10), we found here that ACEA also prevented the inhibition of catalase induced by leptin in a PPAR-␥-mediated manner.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ activates the expression of the antioxidant gene SOD2 that scavenges free radicals and reduces oxidative stress (Ding et al, 2007). Western blot analysis showed that NMDA or OGD/ reperfusion increased the levels of SOD2 in wild-type but not in LMO4-null cortical neurons (Fig.…”
Section: Lmo4 Mediates Ppar␥-dependent Sod2 Upregulation In Neuronsmentioning
confidence: 94%
“…Gal4 and Act fusion protein expression vectors were cotransfected with a Gal4-responsive luciferase reporter (Clontech) and the level of luciferase activity was used as a readout of protein interaction. Luciferase reporter constructs containing the promoter sequences of SOD2-985 to ϩ195 and Ϫ935 to ϩ195 (Ding et al, 2007) were from Qinglin Yang (Morehouse School of Medicine, Atlanta, GA). A bicistronic CMV-LMO4/IRES-GFP expression construct containing mouse LMO4 was generated by PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation